Prolonged Opioid Use Among Opioid-Naive Women Undergoing Breast Reconstructive Surgery - Samuel, Ankhita R.; Fuhr, Laura; DeGeorge, Brent R., Jr; Black, Jonathan; Campbell, Christopher; Stranix, John T. (Archives of Plastic Surgery, 2022)
Background Patients that undergo mastectomy for breast cancer with reconstruction may be prone to prolonged opioid use. As risk factors are not well-established, this article sought to better understand the risk factors that may be associated with this.Methods Patients that underwent breast reconstruction between 2010 and 2018 were identified in PearlDiver, a national insurance claims database. Patient demographics and comorbidities were elucidated, and various complications were then identified. Descriptive statistics as well as a multivariate analysis was used to evaluate the association of risk factors and complications.Results Breast reconstruction patients of 24,765 were identified from this database. Obesity, tobacco use, benzodiazepine use, and anticonvulsant use were all associated with prolonged opioid prescriptions greater than 90 days after both alloplastic and autologous reconstruction.Conclusion Prolonged opioid use continues to remain a topic of concern, and particularly in cancer patients that undergo breast reconstruction. Providers should be aware of potential risk factors for this to reduce this chance following breast reconstruction surgery.
Keywords: prolonged opioid use; breast reconstruction; risk factors